TEACHING CLOUD COMPUTING FOR SOFTWARE ENGINEER’S STUDENTS (Journal of Information Technologies in Education (ITE), 2013)
We suggest content and ways of learning and teaching Cloud Computing course that help to prepare successful software engineers. We consider scheme of the virtualization of laboratory environment that can be used not only for Cloud Computing but also in other courses, when we have to install wide range of software from different software companies.
Keywords: cloud computing; virtualization; laboratory’s environment; hypervisor